PENGALIHAN MAKNA BAHASA INGGRIS ALA JEPANG PADA KANAL YOUTUBE NIHONGO MANTAPPU - Zafir Diva Aliefia; Dwi Anggoro Hadi Utomo (Japanology: The Journal of Japanese Studies, 2025)
Wasei Eigo is a form of Japanese-specific English created by Japanese people by adopting and modifying vocabulary from the origila language. Wasei eigo can be learned through digital media, particularly through videos on channels such as YouTube, This study examines the phenomenon of meaning transfer in wasei eigo and its use on the Nihonggo Mantappu YouTube channel. The objective of this study is to identify the types of wasei eigo that appear and analyze the forms and processes of meaning transfer that occur. This study uses a qualitative descriptive method with a semantic analysis approach. Data was collected from video transcripts on the Nihongo Mantappu channel that contain the use of wasei eigo. The results of the study show that meaning transfer occurs through various mechanism, such as narrowing, broadening, or deviating from the original English meaning. This phenomenon reflects the linguictic and cultural dynamics within Japanese society and demonstrates how digital media plays a role in disseminating forms of language that have undergone local adaptation. Additionally, this study is expected to contribute to linguistic research, particularly in the fields of semantics and Japanese sociolinguistics.